2011
DOI: 10.2485/jhtb.20.259
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Intramuscular Innervation of the Lateral Pterygoid Muscle

Abstract: The lateral pterygoid muscle has unique anatomical, physiological and functional properties. Since it is attached to the temporomandibular joint (TMJ) disc, its pathologies are closely related to TMJ disorders, which affect many people worldwide. Muscle structures and units are characterized by their morphological appearance, nerve distribution and function. In the present study, we examined the intramuscular innervation pattern of the lateral pterygoid muscle using modified sihler's method. Two types of inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Sugisaki et al (1986), Naohara (1989), Wilkinson (1988), Abe et al (1993), Petermann (1994) and Akita et al (2003) did not note facts about age distribution of their examined subjects. Foucart et al (1998), Fujita et al (2001), Akita et al (2003) and Abe et al (2011) gave information about the gender distribution but did not identify a correlation between gender distribution and morphology of the LPM.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Sugisaki et al (1986), Naohara (1989), Wilkinson (1988), Abe et al (1993), Petermann (1994) and Akita et al (2003) did not note facts about age distribution of their examined subjects. Foucart et al (1998), Fujita et al (2001), Akita et al (2003) and Abe et al (2011) gave information about the gender distribution but did not identify a correlation between gender distribution and morphology of the LPM.…”
Section: Resultsmentioning
confidence: 97%
“…2). 11 studies took into account that the LPM may have variations and also considered the relative frequency of each variation (Sugisaki et al, 1986;Naohara, 1989;Wilkinson and Chan, 1989;Abe et al, 1993;Petermann, 1994;Foucart et al, 1998;Fujita et al, 2001;Akita et al, 2003;Pompei Filho et al, 2009;Kiliç et al, 2010;Abe et al, 2011). Sugisaki et al (1986), Naohara (1989), Abe et al (1993), Foucart et al (1998) showed that LPMs may have one, two or three heads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation